2004
DOI: 10.1002/elps.200305909
|View full text |Cite
|
Sign up to set email alerts
|

Mining the human cerebrospinal fluid proteome by immunodepletion and shotgun mass spectrometry

Abstract: We have analyzed the proteome of human cerebrospinal fluid with the help of shotgun mass spectrometry. In order to identify low-abundant proteins in these fluids, we have found it necessary to remove the abundant protein components from the mixture. Immunodepletion of the abundant proteins has allowed us to identify more than 100 proteins in cerebrospinal fluids from a patient suffering from normal pressure hydrocephalus. The identified proteins belong to a variety of different classes ranging from serum prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 16 publications
2
80
0
Order By: Relevance
“…They are represented for example by liquid chromatography [9], binding to solid-phase libraries [10,11], enrichment of low molecular weight proteins [12] or the prior removal of major proteins. The latter is often achieved using immobilized dye [13,14] or immunoaffinity [15][16][17]. Ideally, a depletion technique should be selective and remove 100% of the targeted protein (or proteins) without retaining non-targeted proteins.…”
Section: Introductionmentioning
confidence: 99%
“…They are represented for example by liquid chromatography [9], binding to solid-phase libraries [10,11], enrichment of low molecular weight proteins [12] or the prior removal of major proteins. The latter is often achieved using immobilized dye [13,14] or immunoaffinity [15][16][17]. Ideally, a depletion technique should be selective and remove 100% of the targeted protein (or proteins) without retaining non-targeted proteins.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the problem caused by the large dynamic range of protein expression, several approaches have been developed that will deplete the most abundant proteins from body fluids. In our previous studies, we have shown that an immunoaffinity matrix that is made up of affinity-purified polyclonal antibodies against the six major proteins in serum (HSA, transferrin, haptoglobin, IgG, IgA, and antitrypsin) also removes the six most abundant proteins from CSF and thereby allows the identification by mass spectrometry of a great number of low abundant proteins in CSF (7). Because of its great specificity, we have been using the Multiple Affinity Removal System for all our subsequent studies that are geared toward an in-depth proteome analysis of human CSF.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous CSF proteomic studies, we used immunodepletion followed by shotgun mass spectrometry analysis of the peptide (7). In order to extend our proteome mining efforts and increase the number of identified proteins, we reasoned that further fractionation on the intact protein level of the CSF sample mixture is necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the classical proteomics efforts are geared towards the analysis of the protein constitutes in both CSF and serum (Maccarrone, Birg et al 2004;Maccarrone, Milfay et al 2004), alternative strategies have been established for the identification of novel disease markers for neurological disorders. When it comes to protein analyses, often the concentration plays a significant role in contributing to diagnosis (example -determination of IgG concentration in multiple sclerosis).…”
Section: Single Protein Assaysmentioning
confidence: 99%